Analysis of Spinopelvic Sagittal Balance and Persistent Low Back Pain (PLBP) for Degenerative Spondylolisthesis (DS) following Posterior Lumbar Interbody Fusion (PLIF). (11th January 2020) - He, Shuangjun; Zhang, Yijian; Ji, Wei; Liu, Hao; He, Fan; Chen, Angela; Yang, Huilin; Pi, Bin
Abstract : Objective . To investigate the change of spinopelvic sagittal balance and clinical outcomes after posterior lumbar interbody fusion (PLIF) in patients with degenerative spondylolisthesis (DS), especially the relationship between sagittal spinopelvic parameters and persistent low back pain (PLBP). Methods . 107 patients who were diagnosed with DS and underwent PLIF in our department were enrolled retrospectively in the present study. Sagittal spinopelvic parameters including lumbar lordosis (LL), segmental lordosis (SL), height of the disc (HOD), sacral slope (SS), pelvic incidence (PI), and pelvic tilt (PT) were recorded pre- and postoperatively. Sagittal balance and clinical outcomes were compared between patients with and without PLBP. Pearson correlation was used to analyze the change of sagittal balance parameters and clinical functions. Logistic regression analysis was performed to examine the risk factors of PLBP. Results . It showed significant improvements of SL, HOD, and PT postoperatively. Both the Numeric Rating Scale (NRS) and Oswestry Disability Index (ODI) had significant improvement postoperatively. Change of PT and SL also differed observably between patients with and without PLBP. SL and PT were correlated with NRS and ODI, and insufficient restoration of PT was an independent factor for PLBP. Conclusion . The sagittal balance parameters and clinical outcomes can be improved markedly via PLIF for treating DS. Restoration of SL and PT was correlated with satisfactory outcomes, and adequate improvement of PT may have positive impact on reducing PLBP.